Wpływ przywództwa na sukces organizacji - Skrzypek, Elżbieta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article concerns the role of leadership in the process of developing a successful organization. Some of the problems covered concern the essence of leadership and how it evolved, characteristic features found in leaders, need in leaders to excel organizations they run under changing environment conditions, the role of knowledge acquired by leaders and how it influences the management process. The knowledge itself is an important factor of successful organizations. Thus, intangible assets and knowledge management are in general vital for successful organizations. The role of leadership and recognition of merit in terms of the Polish Quality Award is presented. The role of human resource management and development are chief responsibilities of leaders and need to be addressed in the strategy of every organization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 141-149